The Measuring the success of the implementation of an information and communication technology (ICT)-based management system using the Technology Acceptance Model (TAM) and the Information Security Index (KAMI) at SMK TELKOM Lampung. - IKHSAN, AHMAD (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2024)
The utilization of information and communication technology (ICT) in education, particularly through the implementation of ICT-based management systems in schools, has great potential to improve the quality of learning and school management. However, the success of this system's implementation is also influenced by factors such as ease of use, perceived benefits, and information security levels. This study aimed to measure the success level of the implementation of ICT-based management systems at SMK Telkom Lampung, specifically the My Learning System (MyLMS) learning platform and the Igracias school application. The study employs the Technology Acceptance Model (TAM) to measure user acceptance of the system and the Information Security Index (KAMI) to assess the maturity level of information security. The method was a survey with a quantitative approach, with a sample of 180 respondents, consisting of students, teachers, and administrative staff who actively use the system. The results show that ease of use (average score 10.74) and perceived benefits (average score 13.91) of the system positively affect user acceptance (average score 13.30), which ultimately enhances the perceived quality of the system (average score 143.67). However, the evaluation using the KAMI Index reveals that SMK Telkom Lampung needs to improve its information security management. The total score is 403 out of 645, indicating that SMK Telkom Lampung is at the "Needs Improvement" level. These results indicate that while the ICT-based management system has been well received by users, the aspect of information security still requires improvement to ensure optimal data and information protection